Regioselective Formation of Pyridines by Cycloaddition/Cycloreversion of 1,4-Oxazinone Precursors with Bisalkyne Substrates - Andres, Graydon J.; Anderson, Seth E.; Kinsey, Adrianne M.; Scheerer, Jonathan R. (Synlett, 2024)
This study explores the merged cycloaddition/cycloreversion of a 1,4-oxazinone substrate and conjugated bisalkyne precursors. Good regioselectivity in the Diels–Alder operation is observed and pyridines bearing 3-alkynyl functionality are afforded following cycloreversion and extrusion of CO2. Examples with both symmetric and nonsymmetric bisalkyne substrates are included.
Keywords: 1,4-oxazinone; cycloaddition; cycloreversion; pyridine; Diels–Alder